REGULARISASI SISTEM SINGULAR DENGAN OUTPUT UMPAN BALIK u = Fy + v - Persulessy, Elvinus R. (PATTIMURA UNIVERSITY, 2007)
(E,A,B,C,D) as a singular system is given. E, A, B and C are real constant matrices if E=I, I is a identify matrix, then (E,A,B,C) is a normal system. A unique solution of a singular system exists if (E,A) is regular. A singular system which is regular and the index is not more than one can be simplified to a normal system.The regularization of a singular system by feedback output u = Fy + v is investigated in this paper. Furthermore a sufficient and necessary condition of the existence of F such that (E, A+BFC) is regular and the index is not more than one is represented.